2015
DOI: 10.3945/jn.115.211193
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Uptake of Rectally Administered Butyrate Prevents an Increase in Systemic Butyrate Concentrations in Humans1–3

Abstract: After colonic butyrate administration, splanchnic butyrate release was prevented in patients undergoing upper abdominal surgery. These observations imply that therapeutic colonic SCFA administration at this dose is safe. The trial was registered at clinicaltrials.gov as NCT02271802.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 39 publications
0
41
0
1
Order By: Relevance
“…As such, our data demonstrated a novel interaction between chronic stress, host metabolism and SCFAs, even though more research into the mechanisms involved is warranted in order to understand the exact role of chronic stress in SCFA-host metabolism interactions. Finally, oral SCFA administration itself did not affect faecal SCFA levels, which is probably explained by the rapid uptake of SCFAs (Pouteau et al 2003;van der Beek et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As such, our data demonstrated a novel interaction between chronic stress, host metabolism and SCFAs, even though more research into the mechanisms involved is warranted in order to understand the exact role of chronic stress in SCFA-host metabolism interactions. Finally, oral SCFA administration itself did not affect faecal SCFA levels, which is probably explained by the rapid uptake of SCFAs (Pouteau et al 2003;van der Beek et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate serves as a major energy source for colonic enterocytes and is largely metabolized within the epithelial mucosa (Clausen and Mortensen, 1995; Donohoe et al, 2012). Remaining butyrate is degraded in the liver (Bloemen et al, 2009; van der Beek et al, 2015). Propionate and acetate travel largely intact across the epithelium to the liver, where a substantial portion of propionate is degraded while acetate is released into systemic circulation (Bloemen et al, 2009; Morrison and Preston, 2016).…”
Section: Microbiome-associated Metabolites That Shape the Immune Systemmentioning
confidence: 99%
“…Table 3 shows the results of the several studies that have reported on the concentrations of SCFAs in the portal vein 4, 3436) .…”
Section: Intestinal Bacterial Flora and Short Chain Fatty Acidsmentioning
confidence: 99%